Brand crisis management: the use of information for prevention, identification and management - Salvador, Alexandre Borba; Ikeda, Ana Akemi (Review of Business Management, 2017)
Purpose – To understand, from the management perspective, the use of information on brand crisis management in moments involving prevention, identification and management. Design/methodology/approach – This article is the result of an exploratory, qualitative study. Primary data was collected through interviews with marketing executives and crisis management specialists. Findings – We concluded that managers use information in very different ways, and, taking possession of information and decisionmaking attitudes into account, four groups of crisis managers were found. Originality/value – In order to contribute to the expansion of academic knowledge in the field of marketing administration and brand crisis management, this study presented the crossing of three different fields (information systems, brand crisis management and organizational development) to structure knowledge concerning brand crisis management. From the managerial perspective, certain crises could be avoided by monitoring internal and external information, and by identifying problems in their early stages. From the social perspective, reducing brand crisis cases positively affects society as a whole (organizations and individuals).